Optimization of Fermentation Conditions for Increasing Erucamide Content in Bacillus megaterium Using Several Accelerants - Hao Zhao; Yudan Xie; Zhu Li; Longfeng Wei; Renli Ai (Microorganisms)
As a food packaging sliding agent, erucamide is widely used in the field of food packaging, but the traditional synthesis method of erucamide faces the problems of insufficient raw materials and low yield of colza oil. Our laboratory has found that Bacillus megaterium L2 has the potential to produce erucamide. This study aims to improve the ability of B. megaterium L2 to produce erucamide by adding various accelerants to optimize the fermentation conditions. Univariate and orthogonal tests showed that 0.3% Tween 80, 0.004% Ca2+, 0.04% colza oil, and 0.02% chloroform were the best regulation conditions for erucamide production of the L2 strain, and erucamide content reached 1.778 mg/L, which was 32.59% higher than the blank group and 60.26% higher than before fermentation culture. The mechanism of membrane metabolism in the L2 strain was further investigated, and our data suggested that the conductivity, nucleic acid and protein content, and β-galactosidase activity of L2 were increased significantly after treatment with accelerants, indicating that the accelerants changed the cell membrane permeability of the L2 strain but did not harm or kill the bacteria. Moreover, GC-MS analysis of the cell membrane fatty acids of the L2 strain showed that the ratio of unsaturated to saturated fatty acid components increased from 0.893 to 1.856, which increased the fluidity and reduced the rigidity of the cell membrane. This study could provide some theoretical reference for microbial erucamide fermentation.